2012
DOI: 10.1007/s10195-012-0188-9
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral femoral neck and shaft fracture in children: a report of two cases and a literature review

Abstract: Concomitant ipsilateral fractures of the neck and shaft of the femur in children are rare. The most recent report in this context found a total of only nine reported cases (<12 years of age) following a search of the indexed English literature. These injuries occur in children due to high-velocity trauma, and there is no generally accepted method of treatment. We report three additional cases from the literature and two cases of our own. In our cases, one had a residual 10° varus deformity at the subtrochanter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Thus, this phenomenon demonstrated that a reconstruction nail is a better treatment than a hollow screw+plate with respect to clinical efficacy. This result was similar to that by Song at el., which reported the reconstruction nail was deemed a more efficient therapy than a hollow screw+plate [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this phenomenon demonstrated that a reconstruction nail is a better treatment than a hollow screw+plate with respect to clinical efficacy. This result was similar to that by Song at el., which reported the reconstruction nail was deemed a more efficient therapy than a hollow screw+plate [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of femoral shaft fracture combined with femoral neck fracture, surgery is better than traction. Nonetheless, the reconstruction of the intramedullary nail is an optimal choice [17,18]. The design of the femoral reconstruction intramedullary nail conforms to the physiological axis of the human femur and belongs to the central internal splint frame structure.…”
Section: Discussionmentioning
confidence: 99%
“…McDougall first reported in 1967 a case of ipsilateral femoral neck and shaft fracture in an 8-year-old child, and since then only 16 such cases have been documented. [ 2 , 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no unified view on the mechanism of injury. Song et al [ 3 ] believed that the mechanism of injury involved high energy and impact on both the femoral shaft and neck. In contrast, Hajdu et al [ 4 ] suggested that it resulted from continuous high-energy impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation